The Influence of Internship on The Professionality of Students Departement of Room Division at Batam Tourism Polytechnic - Andriyatno, Valensia Devinsa; Lubis, Arina Luthfini; Fatimah, Zahara (Media Wisata, 2023)
This research aims to analyze the impact of internships on the professionalism of students majoring in the Rooms Division at the Batam Tourism Polytechnic. The research data consists of active students and alumni of the room division program at Batam Tourism Polytechnic university. This research uses a structured questionnaire (58 closed questions assessed using a 4-point Likert scale) which consists of 4 parts: Part I: Internship, Parts II, III and IV are assessments related to professional skills, namely part II: Attitude, part III Discipline and part VI: responsibility. This research uses descriptive statistical analysis. Next, scale measurement analysis is used to check the validity of the research data and the reliability of the questionnaire. Based on the test results using SPSS software, it can be stated that all statement items or questions given from all variables X, Y1, Y2 and Y3 are valid, because the calculated rvalue > rtable. Based on the results of the X and Y reliability tests above, it can be stated that all Cronbach's Alpha values for variables The results of the hypothesis test show that the alternative hypothesis for all variables is accepted. The formulation of the results of the multiple linear regression equation is Y1 = 12.307 + 0.295, Y2 = 7.790 + 0.538 X, and Y3 = 9.932 + 0.418. Internships have an influence of 21.1% in terms of responsibility. The research results illustrate the influence of internships on the professionalism of the rooms division in the hotel department